Vagrants & Accidentals - Craft, Kevin (Book collections on Project MUSE., 2017)
"Vagrants & Accidentals, the second full-length collection from poet Kevin Craft, is part vade mecum, part songbook, whose taut lines and adaptable stanzas traffic in the personal effects of emigration and estrangement, exile and return. In ornithology, a vagrant or accidental is a bird that appears out of its natural or normal range, blown off course by a storm, or inadvertently introduced into a new environment by human trade. Likewise, Craft is interested in things taken out of context--Greek myths in the Pacific Northwest, the potsherd or megalith stranded in a museum, excess carbon in the atmosphere, American pop songs in a Roman piazza, adoptions, estrangements, dangerous migrations, the constant shuffle of human beings from place to place--asking how we reorient ourselves in the crossfire of constant, rapid, global transformation. Organized into four parts, the collection moves from the deeply personal to more global issues of interconnectedness. In language intensely lyrical, grounded in prehistory and science, Craft evokes questions of family and belonging that underscore a lifetime, gradually revealing the forces that shape us from the deepest reaches of time and place. As some birds sing to define their territory, so his poetry calls between the raggedness of daily life and our deeper yearning for coherence."--Amazon.com.